The management of clavicle shaft fractures evaluating : the ability of a novel locked intramedullary device to achieve union and restore function of the shoulder - King, Paul Reginald (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.